KEARIFAN SUFISME DALAM ISLAMISASI JAWA - Purwadi Purwadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article shows the wisdom of Sufism on social transformationin Java at the early spread of Islam. Sufism approach tends to emphasizeon self-awareness while accommodating ornamental outer symbols. Thispattern makes the process of being Muslims in Java more peaceful andacceptable for those who already have certain believe and religion (animism,Hinduism and Buddhism).